STUDI EKSPERIMEN PENGGUNAAN AIR GARAM SEBAGAI SUMBER ENERGI ALTERNATIF - Ali Usman, Muh; Hasbi, Muhammad; Sudia, Budiman (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2017)
The aim of this study was to determine the effect of cross-sectional area of copper and zinc to the brinegenerated power as an alternative energy source.Equipment and materials was used in this studywere theAVO meter, pliers, meter, measuring cups, wells water, salt, copper plate, zinc plate, cables and glass. Theprocedures of this study were to prepare tools and materials, then making an electrochemical cell as much as10 cell container of water and salt using glass, making the series circuit plate of copper and zinc, making asolution of water and salt, then test the salt water as an alternative energy source using AVO meter, Theparameters measured in this study were a big potential and strong electric currents are able to produce brinewith a variety of cross-sectional area of copper and zinc 7 cm2;7 cm2, 7 cm2; 14 cm2, 7 cm2; 21 cm2 and 14cm2; 7 cm2, 14 cm2; 14 cm2, 14 cm2; 21 cm2 and 21 cm2; 7 cm2, 21 cm2; 14 cm2, 21 cm2; 21 cm2. In brinetesting, into energi source, a large power was found on 21 cm2 of 0,899 W elektrode while to increase thepotential value of electric can be done by increasing the number of cells.Keywords: Water, salt, electrochemical cells, alternative energy .